0010 What is the Ideal Bedtime? Data from a Community Sample. (12th April 2019) - Bliznak, Victoria; Perlis, Michael L; Ellis, Jason; Hale, Lauren; Killgore, William D S; Warlick, Chloe; Alfonso-Miller, Pamela; Grandner, Michael A
Abstract: Introduction: Advancing bedtime can decrease sleep efficiency, and the delay of bedtime may result in insufficient sleep. In pursuit of an empirically-supported, real-world bedtime recommendation, the present study examined community-level data on typical bedtime as it relates to sleep problems. Methods: Data from our SHADES study were used for the present analysis, consisting of N=1, 003 working-age adults age 22-60 in the Philadelphia area. Typical bedtime was assessed and compared to insomnia symptoms (Insomnia Severity Index [ISI]), self-reported typical sleep latency, typical wake after sleep onset, sleepiness (Epworth Sleepiness Scale [ESS]), PHQ9 depression scale, and GAD7 anxiety scale. Results were adjusted for age, sex, race/ethnicity, education, and body mass index. Results: Distribution of bedtimes were as follows: ≤8pm=2.4%, 8-10pm=8.5%, 10-11pm=20.4%, 11pm-midnight=29.1%, 12-1am=17.8%, 1-2am=10.9%, and ≥2am=10.9%. Compared to 11pm-midnight, higher ISI scores were seen for ≤8pm (B=4.3, 95%CI[1.79, 6.79], p=0.001), 1-2am (B=2.65, 95%CI[1.36, 3.94], p<0.0005), and ≥2am (B=5.79, 95%CI[4.50, 7.08], p<0.0005). Longer sleep latency was reported by those going to bed ≤8pm (B=14.38, p=0.03), 1-2am (B=8.48, p=0.01), and ≥2am (B=26.88, p<0.0005). Longer WASO was seen for ≤8pm (B=20.76, p=0.04) and ≥2am (B=20.94, p<0.0005). Higher ESS was seen for 1-2am (B=1.16, p=0.02) and ≥2am (B=2.27, p<0.0005). Higher PHQ9 was seen for ≤8pm (B=3.19, p=0.02), 1-2am (B=2.43, p<0.0005), and ≥2am (B=4.47, p<0.0005) and lower PHQ9 was seen for 10-11pm (B=-1.39, p=0.01). Finally, higher GAD7 was seen for 1-2am (B=1.64, p=0.009) and ≥2am (B=2.80, p<0.0005). Lowess plots of continuous values show that the minimum value for ISI and other outcomes seems to occur around 11pm. Conclusion: Overall, those who go to bed at a typical time generally have fewer problems than those who attempt to sleep outside of this window, and in particular those who go to bed close to 11pm have fewer sleep problems and better daytime function. More work examining how modifying bedtimes to promote sleep and daytime functioning is warranted. Support (If Any): R01MD011600, R21ES022931